Students"™ Motivation to Write Argumentative Essay Writing - Surmiyati, Surmiyati; Rezeki, Yanti Sri (Journal of English Education Program, 2024)
Motivation to write argumentative essays constitutes an integral contribution to support students in developing their writing skills. This affective trait needs to be studied as one of the influential supports for language learning. The research focuses on investigating the trend of students"™ level of motivation to write by describing the overall score and the kinds of motivation they employed. The design of the study was quantitative, using a questionnaire delivered to 20 participants. The findings showed that students"™ level of motivation was moderate. Overall, the range of motivation level 3.01 "“ 3.03. The findings indicate that students are motivated to write. The items in each of the components show that the students are willing to receive feedback from the instructors, put a lot of effort into revising their writing by employing strategies to produce better writing, and believe that writing skills are important for future careers. This implication suggests that although students show positive motivation to write, conscious encouragement to be aware of their motivation is needed when dedicating time to writing argumentative writing.